The Tyrosine Kinase Tec Regulates Effector Th17 Differentiation, Pathogenicity, and Plasticity in T-Cell-Driven Intestinal Inflammation - Sandner, Lisa; Alteneder, Marlis; Zhu, Ci; Hladik, Anastasiya; Högler, Sandra; Rica, Ramona; Van Greuningen, Lars W.; Sharif, Omar; Sakaguchi, Shinya; Knapp, Sylvia; Kenner, Lukas; Trauner, Michael; et al. (Frontiers in Immunology, 2021)
T helper (Th) 17 cells are not only key in controlling infections mediated by extracellular bacteria and fungi but are also triggering autoimmune responses. Th17 cells comprise heterogeneous subsets, some with pathogenic functions. They can cease to secrete their hallmark cytokine IL-17A and even convert to other T helper lineages, a process known as transdifferentiation relying on plasticity. Both pathogenicity and plasticity are tightly linked to IL-23 signaling. Here, we show that the protein tyrosine kinase Tec is highly induced in Th17 cells. Th17 differentiation was enhanced at low interleukin-6 (IL-6) concentrations in absence of Tec, which correlates with increased STAT3 phosphorylation and higher Il23r expression. Therefore, we uncovered a function for Tec in the IL-6 sensing via STAT3 by CD4+ T cells, defining Tec as a fine-tuning negative regulator of Th17 differentiation. Subsequently, by using the IL-17A fate mapping mouse combined with in vivo adoptive transfer models, we demonstrated that Tec not only restrained effector Th17 differentiation but also pathogenicity and plasticity in a T-cell intrinsic manner. Our data further suggest that Tec regulates inflammatory Th17-driven immune responses directly impacting disease severity in a T-cell-driven colitis model. Notably, consistent with the in vitro findings, elevated levels of the IL-23 receptor (IL-23R) were observed on intestinal pre- and postconversion Th17 cells isolated from diseased Tec−/− mice subjected to adoptive transfer colitis, highlighting a fundamental role of Tec in restraining IL-23R expression, likely via the IL-6-STAT3 signaling axis. Taken together, these findings identify Tec as a negative regulator of Th17 differentiation, pathogenicity, and plasticity, contributing to the mechanisms which help T cells to orchestrate optimal immune protection and to restrain immunopathology.